2020
DOI: 10.1152/ajpregu.00245.2019
|View full text |Cite
|
Sign up to set email alerts
|

Low-calorie sweeteners cause only limited metabolic effects in mice

Abstract: There are widespread concerns that low-calorie sweeteners (LCSs) cause metabolic derangement. These concerns stem in part from prior studies linking LCS consumption to impaired glucose tolerance in humans and rodents. Here, we examined this linkage in mice. In experiment 1, we provided mice with chow, water, and an LCS-sweetened solution (saccharin, sucralose, or acesulfame K) for 28 days and measured glucose tolerance and body weight across the exposure period. Exposure to the LCS solutions did not impair glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
3
12
0
1
Order By: Relevance
“…Consistently, modulation of the gut microbiota was found in other rodent studies upon saccharin consumption, as a minor fraction of saccharin is not absorbed and will concentrate in the colon (96,127). Besides saccharin, sucralose was consistently found to affect microbiota in mice as it accumulates in the colon (85,88,96). However, contradictory results regarding the effect of acesulfame-K on gut microbiota composition have also been found in rodents (85,86).…”
Section: The Interaction Between Artificial Sweeteners Gut Microbiotsupporting
confidence: 68%
See 3 more Smart Citations
“…Consistently, modulation of the gut microbiota was found in other rodent studies upon saccharin consumption, as a minor fraction of saccharin is not absorbed and will concentrate in the colon (96,127). Besides saccharin, sucralose was consistently found to affect microbiota in mice as it accumulates in the colon (85,88,96). However, contradictory results regarding the effect of acesulfame-K on gut microbiota composition have also been found in rodents (85,86).…”
Section: The Interaction Between Artificial Sweeteners Gut Microbiotsupporting
confidence: 68%
“…specifically, one study that used the ADI-dosage for human consumption (15 mg/kg/day) showed no effect on body weight in mice after 8 weeks of acesulfame-K consumption, while another study shows an increase in body weight by exceeding the ADI more than 2-fold (37.5 mg/kg/day) after 4 weeks in mice (85,86). Furthermore, saccharin consumption was found to increase body weight in mice compared to water, sucrose or glucose, whereas other studies in rodents have shown reduced or unchanged body weight compared to mice receiving water, glucose, fructose or sucrose (87)(88)(89)(90)(91)(92)(93)(94). However, the absorption of saccharin is lower in rodents compared to humans due to a relative higher stomach pH in rodents (92).…”
Section: Body Weight and Adipositymentioning
confidence: 91%
See 2 more Smart Citations
“…However, it is noticeable that, among these numerous studies, there is no reproducible microbiota signature even for commonly studied NCAS, such as sucralose [ 49 , 51 , 52 , 87 ]. The consequences of these microbiota alterations on glucose tolerance were not assessed in these reports, except for one that found no effect on glucose tolerance (OGTT) after 6 weeks of sucralose supplementation in ileitis-prone SAMP mice [ 52 ] that is consistent with other independent reports which showed that consumption of NCAS, such as sucralose or aceK, has either a minor [ 82 ], or no effect [ 81 ] on glucose tolerance.…”
Section: Discussionmentioning
confidence: 75%